The Concept of Cyber Insurance as a Loss Guarantee on Data Protection Hacking in Indonesia - Puluhulawa, Jufryanto; Muhtar, Mohamad Hidayat; Towadi, Mellisa; Swarianata, Vifi; Apripari (Law, State and Telecommunications Review, 2023)
[Purpose] This research departs from the legal vacuum regarding data protection insurance in Indonesia. In terms of regulation, Law Number 40 of 2014 concerning Insurance has not regulated all about cyber insurance, and Indonesia still needs to have a law that regulates data protection. [Methodology/Approach/Design] This research is categorized into the normative legal research type based on the issues and themes raised as a research topic. The research approach used is the conceptual approach, philosophical approach, and analytical approach. The research focuses on analyzing the concept of cyber insurance in protecting data and a study of the urgency of regulating cyber insurance in Indonesia to minimize the impact of losses due to data hacking. [Findings] The results show that the concept of cyber insurance in personal data protection began in the 80s and increased in the early 2000s due to digitization in all areas of people’s lives. This significant development was not followed by Indonesia, with a legal vacuum regulating cyber insurance in data protection. Therefore, several things that Indonesia must do, namely Revision of the Law of the Republic of Indonesia Number 40 of 2014 concerning Insurance, Establishment of implementing regulations, need new normalization in overriding the Civil Code. [Practical Implications] This study has legal implications for norming. In addition, it has implications for changes in the concept of insurance in Indonesia because, so far, cyber insurance services are still conventional. [Originality/Value] On an Indonesian scale, this research is the first to comprehensively discuss cyber insurance for data protection.